Investigation of Social Activity and Meeting Platforms in the Pandemic Process in Terms of Library Services - GÜNEŞ, GÜSSÜN (My University, 2021)
Scientific and professional organizations play an important role in the exchange of ideas and information in the world of science. In the librarian profession, organizations organized by the efforts of professional associations are very important for the development of the profession and the interaction of librarians. The COVID-19 pandemic has affected many parts of our lives. Following social distance rules, many organizations have moved face-to-face events to online meetings. While the COVID-19 pandemic has stopped traditional face-toface conferences for the foreseeable future, the growth of online conferencing has highlighted many drawbacks associated with face-to-face format and demonstrated the advantages of taking these events online. Online formats have enhanced conferences using a range of audio-visual technologies to facilitate real-time conversations, extended question-answer sessions, electronic posters and discussion platforms, educational workshops, events such as professional and academic networking, experience sharing, and virtual industry exhibitions. Online conferences have removed barriers by reducing both costs and travel times. In this study, we will explain how online conferences are more inclusive, more cost-effective, less time consuming, and more accessible to researchers around the world, especially early in their career. The tips presented here will not only be useful for future online meetings, but will also provide options for future such events as online or hybrid models for sustainability. Within the scope of the study scientific online activities in the field of medical and health sciences librarianship will be examined. The experiences of the “EAHIL 2021 Virtual Workshop” Organization Committee will be included by examining the literature produced within the scope of online event management. The new way of interaction between academics and professional platforms with online organizations can be considered as part of a system of resistance that was previously neglected and should become part of routine practice in the scientific community. The emerging online technologies cannot be expected to completely replace or take the place of face-to-face scientific and professional activities. However, face-to-face meetings are not susceptible to poor internet connectivity issues and offer new opportunities for socializing, creating new collaborations and sharing ideas. We think that the structure of scientific meetings will be re-examined upon the end of the COVID-19 epidemic. You can attend multiple conferences to help your professional development needs along with online events. This is reflected not only in alleviating the barriers to attending traditional physical conferences, but also in introducing new and more importantly accessible opportunities for young scientists to create a niche in the academic meeting landscape. Conclusion Sharing more experience with online event management will provide important tips for future online meetings. At the same time, these studies, which are brought to the literature, will contribute to the planning of online activities in the best way.
Keywords: Covid-19; Pandemics; Videoconferencing / Organization & Administration; Social Isolation; Virtual Workshop